Effect of Dietary Coriander Seeds Supplementation on Growth Performance Carcass Traits and Some Blood Parameters of Broiler Chickens - Saeid, J.M.; AL-Nasry, A.S. (International Journal of Poultry Science, 2010)
A trial was conducted to determine the effect of different levels of coriander seed supplementation in diets on performance and blood parameters in broilers. Two hundred and fourty (1-day old) commercial broiler chicken (ROOS) were divided into groups of 60 birds in each and randomly assigned to four treatment diets with three replicate. Birds were fed basal diets or the basal diet supplemented with 0.1, 0.2 and 0.3% of coriander seed. Experiment was continued 42 days. Birds that fed 0.3% coriander seed diet exhibited the largest body weight gain, feed conversion ratio and carcass yield and decreased feed intake and fat pad (%BW). There was differences in PCV%, RBC counts and Hb concentration in 0.3% coriander seed supplemented groups, but differences of the other group were not statistically important. There was no different in total number of WBC, H/L as well as H/L ratio among the treatment groups. There was no significant difference for GPT and GOT enzyme activity between the treatments. The coriander seed supplementation also led to decrease the glucose and cholesterol concentration in blood serum. Based on the results of this study, it could be advised to supplement broiler feed with 0.3% coriander seed.